Seasonal cycle of zooplankton standing stock inferred from ADCP backscatter measurements in the eastern Arabian Sea. (April 2022) - Aparna, S.G.; Desai, D.V.; Shankar, D.; Anil, A.C.; Dora, Shrikant; Khedekar, R.
Abstract: We use ADCP (acoustic Doppler current profiler) backscatter, measured during October 2012 to December 2020 at three locations on the continental slope in the eastern Arabian Sea (EAS), to study the seasonal variation in zooplankton standing stock. The regression from backscatter to biomass is based on zooplankton sampling at these locations off Mumbai (northern EAS or NEAS), Goa (central EAS or CEAS), and Kollam (southern EAS or SEAS). Analysis of the data over 24–140 m shows that the backscatter and zooplankton biomass decrease from the upper ocean, whose bottom is denoted roughly by 215 mg m −3 biomass contour, to the thermocline; this decrease in biomass with depth is weaker in the SEAS. The standing stock, defined as the integral of the biomass over 24–120 m, varies seasonally in the NEAS and CEAS, but the seasonal cycle is weaker in the SEAS. The minimum of standing stock is attained towards the end of the summer monsoon and the maximum occurs during the winter monsoon. This seasonal variation of the standing stock is also evident in a monthly climatology. Since the biomass changes less from the upper ocean to the thermocline in the SEAS, the seasonal range of standing stock is lower in the SEAS compared to the CEAS or NEAS. Analysis shows a high correlation between the depth of the 215 mg m −3 biomass contour and standing stock in the NEAS and CEAS; this relation is weaker in the SEAS. This seasonal variation of the standing stock is in contrast to that of satellite-derived chl- a, which peaks in the EAS during the summer monsoon. Highlights: We map the seasonal variation of zooplankton biomass and standing stock in the EAS. Biomass decreases with depth till thermocline, but this trend is weaker in the SEAS. Standing stock in NEAS and CEAS is maximum (minimum) during winter (summer) monsoon. The seasonal variation of standing stock is weaker in the southeastern Arabian Sea. This variation of standing stock is in contrast to that of satellite-derived chl-a.